An empirical test of stage models of e-government development: Evidence from Dutch municipalities. Issue 4 (8th August 2017) - Rooks, Gerrit; Matzat, Uwe; Sadowski, Bert
ABSTRACT: In this article we empirically test stage models of e-government development. We use Lee's classification to make a distinction between four stages of e-government: informational, requests, personal, and e-democracy. We draw on a comprehensive data set on the adoption and development of e-government activities in 510 Dutch municipalities over the period 2004–2009. Our results show that progression through stages of e-government is mostly linear. However, it seems that a single dimension is insufficient to explain e-government development at the level of more specific features of e-government. Our analysis demonstrates that municipalities sometimes adopt certain e-government features at a later stage even if features of an earlier stage are not adopted at all. These findings suggest that municipalities can—at the level of e-government features—immediately proceed to later stages without having to pass through earlier stages. We conclude that stage models may have some value for benchmarking municipalities at the level of stages, but are inadequate in explaining or predicting the development of features at the different e-government stages.